Analysis of the digit ratio association with success in Olympic wrestling - Torres-Bonete, M.; Pallares, J. G.; Lopez-Gullon, J. M.; de la Cruz-Sanchez, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The second-to-fourth digit ratio (2D:4D) has been reported to be negatively correlated with sport performance in male and female athletes across a variety of endurance and team sports (Manning and Taylor, 2001), even when physical factors and effort, cognitive, and personality variables are controlled (Testern and Campbella, 2001). Therefore, the aim of this study was to analyse the contribution of the 2D:4D to success in Olympic wrestling. Methods: A total of 180 wrestlers that took part in the 2011 Spanish Wrestling Championship, in one of the three Olympic wrestling styles, participated in the study: Greco-Roman Male (GRM), n = 60; Freestyle Male (FSM), n = 72; and Freestyle Female (FSF), n = 48. According to the tournament results, two different competitive levels (i.e., successful and nonsuccessful) were established in each wrestling style and weight category for subsequent comparisons. Successful groups of wrestlers were formed from the four medal winners (i.e., 1st, 2nd, and the two 3rd classified) in each of the 7 weight categories for both male styles (GRM and FSM) and the female style (FSF). Prior to competition, wrestlers were interviewed about their years of training experience and their hands were scanned. 2D:4D was calculated using computer-assisted image analysis (Allaway et al., 2009). A multinomial logistic regression coefficient to calculate odd ratios (OR`s) and 95% confidence intervals (CI`s) were established to determine the contribution of 2D:4D and training experience to success in Olympic wrestling. Results: We found differences between genders and we could determing that 2D:4D was greater in men than women in both hands (right hand t-test p=0.009, t=-2.63; left hand t-test p=0.015, t=-2.45). There were no differences between successful and non-successful wrestlers in 2D:4D in any wrestling style (GRS, FSM and FSF) (p=0.87 for right hand, and p=0.46 for left hand), whereas having high training experience supposed an increase up to 4.38 (1.70 - 11.01) times more likely to be successful. Discussion: As a possible marker of prenatal testosterone exposure (which could be a key factor in strength development), 2D:4D has been proposed as an indirect measure which can discriminate an exceptional and talented genotype for sport participation (Testern and Campbella, 2001). However, the main finding of the present study was that 2D:4D is not a valid assessment to discriminate successful and non-successful wrestlers, while training experience is a good predictor of competition prowess in that kind of highly trained athletes.